IDENTIFICATION AND MAPPING OF DUSUNG SYSTEM AS LOCAL CULTURE-BASED AGROFORESTRY IN AMBON CITY, MALUKU PROVINCE, INDONESIA - Angela Martha Rettob; Regan Leonardus Kaswanto; Efi Yuliati Yovi (Indonesian Journal of Forestry Research, 2026)
Dusung, a traditional agroforestry system in Maluku, represents a unique cultural heritage shaped by shifting cultivation and patrilineal land ownership. Adapted to the ecological conditions of small islands, dusung has demonstrated environmental benefits such as maintaining soil fertility, regulating hydrological functions, preventing erosion, enhancing local income, and conserving biodiversity. Despite its ecological and socio-cultural importance, data on the structure, composition, and spatial distribution of dusung agroforestry, particularly within watershed areas, remains scarce. This study aims to identify and map dusung agroforestry patterns based on local wisdom in the Wai Batu Gajah Watershed, Ambon City. The research employed field surveys, vegetation analysis, and structured interviews with 30 dusung farmers to explore management practices rooted in traditional knowledge. Vegetation assessments revealed moderate species diversity, with dominant species including durian (Durio zibethinus), gandaria (Bouea macrophylla), mangosteen (Garcinia mangostana), kecapi (Sandoricum koetjape), langsat (Lansium domesticum), aren palm (Arenga pinnata), and salak (Salacca zalacca). Spatial analysis of 25 dusung areas delineated based on dati (customary land units) highlights how traditional land tenure and customary institutions play a central role in sustaining the dusung system. The mapping further illustrates that the distribution of dusung reflects deep-rooted cultural patterns in managing natural resources. These findings underscore the need for further research integrating ecological, economic, and socio-cultural dimensions to support the long-term sustainability of dusung agroforestry through culturally appropriate conservation strategies.